Optimizing the Extraction of Polyphenols from Different Edible Lichens Using Response Surface Methodology and the Determination of Their Mineral and Antibacterial Properties - Ozkan, Kubra; Bekiroglu, Hatice; Cebi, Nur; Bozkurt, Fatih; Dere, Sevda; Ozdemir, Hilmi; Arici, Muhammet; Karasu, Salih; Sagdic, Osman (MDPI, 2025)
This study employed response surface methodology for the first-time optimization of the ultrasound-assisted extraction (UAE) of the total phenolic content (TPC) and ABTS from edible lichens, including Evernia divaricata, Evernia prunastri, Pseudevernia furfuracea, Bryoria fuscescens, and Lobaria pulmonaria. Fourteen experimental points were generated using Design Expert Software, with the extraction temperature (25-40 degrees C), extraction time (5-20 min), and ethanol concentration (0-80%) as independent variables, and TPC and ABTS as dependent variables. The phenolic profile and mineral and antibacterial properties of the optimized lichen extracts were determined. Evernic and usnic acid were found in Evernia species. Atranorin was detected only in P. furfuracea. Fumarprotocetraric acid was found exclusively in B. fuscescens and was not detected in any of the other lichens. Calcium was found to have the highest mineral content in all the lichens, followed by potassium. L. pulmonaria, showing the lowest inhibition effect against all tested bacteria, while E. divaricata exhibited the most effective inhibition.
Keywords: ultrasound-assisted extraction; optimization; phenolic profile; volatile compound; mineral content; FATTY-ACID-COMPOSITION; FURFURACEA L. ZOPF; ANTIOXIDANT ACTIVITY; PSEUDEVERNIA-FURFURACEA; ANTIMICROBIAL ACTIVITY; ASSISTED EXTRACTION; EVERNIA-PRUNASTRI; HYPOGYMNIA-PHYSODES; PHENOLIC-COMPOUNDS; MAJOR METABOLITES; Food Science & Technology